Pola Komunikasi Keluarga Pernikahan Beda Etnis Rote dan Timor Di Kelurahan Naikoten Satu - Rendy Hermanto Abraham (Universitas Kristen Satya Wacana, 2020)
This research emphasizes on how the communication patterns that occur in inter-ethnic marriages between Rote people and Timorese in the village of Naikoten Satu. By using an interpretive approach, the respondents who are the object of research methodologically will understand and describe the communication patterns that occur in families of different ethnicities. In dealing with the problem of inter-ethnic communication, in the context of inter-ethnic marriage, stereotypes can influence the extended family's assessment of someone who will become a life partner. The difficulty of inter-ethnic marriages between ethnic groups itself is sometimes based on excessive stereotypes in each ethnic group. Where in the two tribes, namely Rote and Timor, there are stereotypes that affect the views of people from other tribes towards them. For example, in the Rote people, most people think that some of the words of the Rote people cannot be trusted or are labeled a fraud, while in the Timorese most people think that the Timorese are a tribe with a low educational background. So it is interesting to study how the communication patterns that occur in the inter-ethnic marriage family. In this study the researcher used four communication patterns according to Joseph DeVito, namely Separately Balanced communication patterns, Separately Balanced communication patterns, Separate Unbalanced communication patterns and Monopoly Communication patterns. The results of this study indicate that inter-ethnic marriages between Rote and Timorese tend to use a separate balanced communication pattern. This is in accordance with the assumptions of the theory, namely that in the family the equality of the relationship is maintained, but each person has the authority and control in their respective fields. This is also supported by the findings of field data, namely the distribution of control and authority between husband and wife. One example is in terms of matters concerning the needs of the wife's child who has greater authority, whereas in terms of work or matters relating to the husband's income, it is the wife who has the authority